2016
DOI: 10.1016/j.ajog.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infection following hysterectomy: adjusted rankings in a regional collaborative

Abstract: After adjusting for patient-related factors and site variation, more than 40% of hospitals will change quartile rank with respect to deep surgical site infection. Identifying a quartile of hospitals that are statistically different from others was not feasible in our collaborative because only 2 of 12 hospitals were outliers. These findings suggest that under the Hospital Acquired Condition Reduction program, many hospitals will be unjustly penalized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…This may be due to the patient mix in our study, which included both gynecological and obstetric surgeries. A regional collaborative data from USA did not show any difference in age of the women having SSI following hysterectomy [28]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be due to the patient mix in our study, which included both gynecological and obstetric surgeries. A regional collaborative data from USA did not show any difference in age of the women having SSI following hysterectomy [28]…”
Section: Discussionmentioning
confidence: 99%
“…Longer operative time by more than 30 min increases the risk for SSI (OR 1.30) [28]. Another study identified that an operative time longer than 75th percentile increased the risk of SSI by 1.84 times compared to vaginal approach [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In present study, a significant association was 144 observed between higher ASA grade and prevalence of SSI (Grade I, II and III: 4.3%, 23.1% & 20%; p<0.05). Various studies have shown that ASA score greater than 2 is a risk factor for development of SSIs [28][29][30][31]. Morgan et al [28] in their study observed that ASA score of more than two was associated with increase in risk of SSI by 1.52 times.…”
Section: Discussion:-mentioning
confidence: 98%
“…Various studies have shown that ASA score greater than 2 is a risk factor for development of SSIs [28][29][30][31]. Morgan et al [28] in their study observed that ASA score of more than two was associated with increase in risk of SSI by 1.52 times. A study on SSI following cesarean section from Tanzania showed that ASA score more than 3 had about 2.7 times higher risk for SSI [29].…”
Section: Discussion:-mentioning
confidence: 98%